NFPOS and Their Anti-Corruption Disclosure Practices: Evidence from Australia - Islam, M.; Haque, S.; Gilchrist, David (Routledge, 2016)
By focusing on major Australian overseas aid not-for-profit organisations (NFPOs), this study has found that NFPOs’ public disclosures lack appropriate commentary relating to anti-corruption measures. We found that this could be due to a break down in regulatory oversight caused by a lack of mandatory reporting standards. This finding reinforces the experience of NFPOs in terms of addressing anti-corruption issues. The key lesson is that there is a need for significant improvement in the anti-corruption regulations, hence associated disclosure practices within the NFPOs sector.